Corruption and Crime: Upshot on the Standard of Education in Nigeria (Case Study of Imo State University, Owerri): corruption and crime in schools - Ihenetu, Stanley; Samuel E., Opara; R., Urenyere (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2020)
The quality and standard of education in Nigeria is one of the most pressing subjects in the minds of Nigerians who value education as far as education is concerned. Inferable from the escape clauses found in the educational arrangement of Nigeria today. Like, silly alumni, absence of legitimate educational direction on understudies and educators, deficient norm and accessibility of educational offices, arrangement of inadequate educational framework, degenerate educational personals or expert and so forth In any case, there are a few educational wrongdoings and debasement that militate against the achievement and acknowledgment of the ideal norm of training in Nigeria. A portion of these violations are pay off, cultism, drug misuse, lewd behavior/indiscrimination, assessment misbehavior from staff and understudies separately, theft of assets and so forth Consequently, in this undertaking, the specialist is examining about the falling norm of instruction because of wrongdoing, the different kinds of wrongdoing found in the educational framework and proffered answer for a decrepit educational framework. Despite the fact that, checking these educational wrongdoings and defilement should be an aggregate obligation of the guardians, educators, strict pioneers, specialists of the establishments just as the public authority. From the result obtained in this study, the Chi-square value calculated is greater than expected (critical), therefore the null hypothesis was reject and conclude that the low standard of education is as a result of crimes and corruption in the sector.